FORMULASI INSEKTISIDA NABATI MINYAK BUNGKIL MIMBA DENGAN SURFAKTAN DEA - Yusriah, Erliza Hambali, dan Dadang (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Neem cake oil has an active compound in form 242.2 ppm azadirachtin. The active compound has activity as feeding inhibitor, nesting rejection, growing inhibitor and mortality effects of many insect pests. Therefore, neem cake was extracted to produce oil. The purpose of this research was to obtain the best ratio of extraction oil from neem cake by maceration method and oil neem cake formulated by DEA surfactant. The oil extraction from neem cake was undertaken by maceration method using a solvent like n-hexane and produce the greatest yield at comparison neem cake and n-hexane 1:4 (w/v). The oil was produced from extraction of neem cake was solid form at room temperature, so it was added a general solvent as usually used in the pesticide industry to dissolved. i.e. Solvesso. The concentration of DEA surfactant used in neem cake oil formulation was 8%. The bioinsecticide formulations of this research was 8% DEA, 15% for oil neem cake and 15% for Solvesso in 30 g formulations .Keywords: DEA surfactant, insecticide formulation, maseration method, neem seed oil